The Psychological Aspects of Virtual Office at Home for Employees and Employers During The COVID-19 Pandemic - Yuliana Yuliana (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: The COVID-19 pandemic has made changes to all aspects of life. Work must be done at home or somewhere outside the office. Although a virtual office is mostly done from one’s home, it can be done anywhere. The aim of this paper is to describe the positive and negative psychological aspects when implementing virtual offices at home for employees and employers during the COVID-19 pandemic. Background Problems: A virtual office has commonly been used during the pandemic condition. Many psychological aspects of a virtual office can affect the employee and his/her family. The impacts can be both positive and negative. Research problem: There are negative impacts, from a psychological aspect, of creating a virtual office at home besides the positive values. Novelty: This paper highlights the psychological aspects when implementing a virtual office at home. People often think that working from home has no challenges at all; it is considered to be more flexible and comfortable. On the other hand, working from home has many aspects that should be considered from the employees’ and employers’ views. Research Methods: This is a narrative literature review. Various types of literature were taken from the Science Direct and Google Scholar databases. Inclusion criteria were research and review articles. Exclusion criteria were un peer-reviewed articles and unavailable full texts. To maintain the quality of the paper, all the articles were read twice. The articles were categorized in a table, summarized, and then narrated. Finding/Results: The positive psychological impacts are flexibility, creativity, and independence. A worker can creatively manage his/her time accordingly, to create a life balance between work and family. The negative psychological impacts are life-work conflicts, burnout, and the autonomy-paradox. Conclusion: The essential keys for a virtual office’s implementation are resilience, creativity, flexibility, and adaptation. The use of a virtual office may continue, due to time and financial efficiencies, despite the COVID-19 pandemic ending.